Kratom Dependence in Adolescents: Is Methadone A Lifesaver? (Bangladesh Journal of Medical Science, 2021)
Kratom dependence among adolescent, even though underreported, is increasing in prevalence in Southeast Asia. Kratom can be simply misused with a great possible addiction and subsequently cause serious undesirable physical and mental health consequences, which is not something to be taken lightly. We present three case series of late adolescents who consumed kratom for more than six months, which leads to poor school performance and had already developed withdrawal symptoms. This case series illustrates the effectiveness of treating adolescents with kratom dependency using combination of medical therapy - Methadone as Drug Substitution Therapy (DST) and supportive therapy from their family members. Therefore, it is crucial for primary care practitioners to screen the adolescents and alert the withdrawal symptoms as well as initiating early discussion with psychiatrist in order to start the prompt treatment since DST is available in primary care clinic.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.673-677